Recent advances in bioethanol production from lignocelluloses: a comprehensive review with a focus on enzyme engineering and designer biocatalysts - Lugani, Yogita; Rai, Rohit; Prabhu, Ashish A.; Maan, Poonam; Hans, Meenu; Kumar, Vinod; Kumar, Sachin; Chandel, Anuj Kumar; Sengar, R. S. (Green Wave Publishing of Canada, 2020)
Many countries have their biofuel policy programs in place as part of their overall strategy to achieve sustainable development. Among biofuels, bioethanol as a promising alternative to gasoline is of substantial interest. However, there is limited availability of a sufficient quantity of bioethanol to meet demands due to bottlenecks in the present technologies to convert non-edible feedstocks, including lignocelluloses. This review article presents and critically discusses the recent advances in the pretreatment of lignocellulosic biomass, with a focus on the use of green solvents, including ionic liquids and deep eutectic solvents, followed by enzymatic saccharification using auxiliary proteins for the efficient saccharification of pretreated biomass. Different techniques used in strain improvement strategies to develop hyper-producing deregulated lignocellulolytic strains are also compared and discussed. The advanced techniques employed for fermentation of mixed sugars contained in lignocellulosic hydrolysates for maximizing bioethanol production are summarized with an emphasis on pathway and transporters engineering for xylose assimilation. Further, the integration of different steps is suggested and discussed for efficient biomass utilization and improved ethanol yields and productivity.
Keywords: Integrated fermentation; Transporter engineering; Pathway engineering; Auxiliary proteins; Enzymatic saccharificatio; Pretreatment